2020
DOI: 10.1186/s12889-020-09648-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception during the 2014–2015 Ebola outbreak in Sierra Leone

Abstract: Background Perceived susceptibility to a disease threat (risk perception) can influence protective behaviour. This study aims to determine how exposure to information sources, knowledge and behaviours potentially influenced risk perceptions during the 2014–2015 Ebola Virus Disease outbreak in Sierra Leone. Methods The study is based on three cross-sectional, national surveys (August 2014, n = 1413; October 2014, n = 2086; December 2014, n = 3540) that measured Ebola-related knowledge, attitudes, and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…internet, text messages), and accessed three or more information sources. Television, radio, house visits by health workers and government campaigns, and using two or less information sources appeared to have no influence on perceived risk [ 68 ]. Two studies showed inconsistent effects of newspapers, brochures and billboards on risk perception [ 60 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…internet, text messages), and accessed three or more information sources. Television, radio, house visits by health workers and government campaigns, and using two or less information sources appeared to have no influence on perceived risk [ 68 ]. Two studies showed inconsistent effects of newspapers, brochures and billboards on risk perception [ 60 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Television, radio, house visits by health workers and government campaigns, and using two or less information sources appeared to have no influence on perceived risk [ 68 ]. Two studies showed inconsistent effects of newspapers, brochures and billboards on risk perception [ 60 , 68 ]. Previous community experience of disease [ 55 ] and exposure to a new and unfamiliar disease [ 67 ] were associated with increased risk perception.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations